The Role of Caregiver in Patients of Nasopharyngeal Cancer (NFC) During Treatment - Harsudianto Silaen; Melva Epy Mardiana Manurung (Jurnal KESANS : Kesehatan dan Sains, 2022)
Nasopharyngeal cancer patients with stage I – IV will cause painful symptoms such as signs of swelling due to the growth of abnormal tissue in the nasopharynx. Symptoms of nasopharyngeal cancer can interfere with daily activities, the fulfillment of daily needs, and the need for rest. The dependence of nasopharyngeal cancer patients with stage I – IV is very minimal to carry out daily activities both physically, psychologically, socially, and in control of disease or symptoms related to treatment and care. This study aims to explore in-depth the meaning of the experience of a partner with nasopharyngeal cancer as a caregiver at home. This research is a descriptive phenomenological study. Data was collected by depth interviews and field notes. The participants in this study were 10 people who were selected by the purposive sampling technique. The data obtained were analyzed using the Colaizzi approach. The results of the research analysis found 3 themes, namely helping patients in meeting basic needs, impact on caregivers, and wisdom for caregivers. In general, caregivers feel neglected, lack information on how to care for their partner with nasopharyngeal cancer and the use of health care facilities. Based on the results of the study, it is suggested that couples should be more informed about the disease of partners who have nasopharyngeal cancer in the form of health education.